Management and outcomes of patients admitted with type 2 myocardial infarction with and without standard modifiable risk factors. (15th January 2023) - Sokhal, Balamrit Singh; Matetić, Andrija; Paul, Timir K.; Velagapudi, Poonam; Lambrinou, Ekaterini; Figtree, Gemma A.; Rashid, Muhammad; Moledina, Saadiq; Vassiliou, Vassilios S.; Mallen, Christian; Mamas, Mamas A.
Abstract: Background: Whilst it is known patients without standard modifiable cardiovascular risk factors (SMuRF; hypertension, diabetes, hypercholesterolaemia, smoking) have worse outcomes in Type 1 acute myocardial infarction (AMI), the relationship between type 2 AMI (T2AMI) and outcomes in patients with and without SMuRF is unknown. This study aimed to determine the prevalence, characteristics and clinical outcomes of patients hospitalised with T2AMI based on the presence of SMuRF. Methods: Using the National Inpatient Sample, all hospitalizations with a primary discharge diagnosis of T2AMI were stratified according to SMuRF status (SMuRF and SMURF-less). Primary outcome was all-cause mortality while secondary outcomes were major adverse cardiovascular and cerebrovascular events (MACCE), major bleeding and ischemic stroke. Multivariable logistic regression was used to determine adjusted odds ratios (aOR) with 95% confidence intervals (95% CI). Results: Among 17, 595 included hospitalizations, 1345 (7.6%) were SMuRF-less and 16, 250 (92.4%) were SMuRF. On adjusted analysis, SMuRF-less patients had increased odds of all-cause mortality (aOR 2.43, 95% CI 1.83 to 3.23), MACCE (aOR 2.32, 95% CI 1.79 to 2.90) and ischaemic stroke (aOR 2.57, 95% CI 1.56 to 4.24) compared to their SMuRF counterparts. Secondary diagnoses among both cohorts were similar, with respiratory disorders most prevalent followed by cardiovascular and renal disorders. Conclusions: T2AMI in the absence of SMuRF was associated with worse in-hospital outcomes compared to SMuRF-less patients. There was no SMuRF-based difference in the secondary diagnoses with the most common being respiratory, cardiovascular, and renal disorders. Further studies are warranted to improve overall care and outcomes of SMuRF-less patients. Graphical abstract: Unlabelled Image Highlights: SMuRF-less patients represent 7.6% of T2AMI admissions. SMuRF-less patients admitted with T2AMI experience more adverse outcomes. There was no SMuRF-based difference in secondary diagnoses between each group.